Light-operated liquefied hydrogel for inhibiting formation of scar on wound surface as well as preparation method and application of light-operated liquefied hydrogel
By light-controlled liquefaction of hydrogel and using PDA@CeO2-SAB nanoparticles to release drugs under near-infrared light activation, CD36 expression is inhibited, solving the scar formation problem of existing therapies that are expensive and have large side effects, and achieving economical and safe scarless wound repair.
Patent Information
- Application Number
- CN202511211452.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-28
- Publication Date
- 2025-10-10
- Estimated Expiration
- 2045-08-28
AI Technical Summary
Existing clinical therapies have a high success rate in preventing and treating scar formation but are expensive and accompanied by adverse reactions. There is a lack of economical, safe and effective drug delivery systems to achieve scarless wound repair.
A light-controlled liquefied hydrogel containing PDA@CeO2-SAB nanoparticles, borate borax buffer with a pH of 8.2-8.6, and PVA hydrogel is used. It is activated by 808 nm near-infrared light to achieve precise drug release and inhibit CD36 expression, thereby promoting wound healing.
It provides a hydrogel with good shape adaptability and strong adhesion, precise drug release, reduced inflammatory response, promoted wound healing, inhibited scar formation, good biocompatibility and few side effects.
Smart Images

Figure CN120754311A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of biomedical materials, and in particular relates to a light-controlled liquefied hydrogel for inhibiting scar formation on wound surfaces, and a preparation method and application thereof. Background Art
[0002] Wound healing progresses through four phases: coagulation, inflammation, proliferation, and remodeling. During the coagulation phase, platelets aggregate and produce PDGF, which, along with bacterial products, recruits inflammatory cells to the site of injury. Inflammatory cells aggregate and secrete proinflammatory cytokines, leading to the proliferation phase. Epidermal cells, fibroblasts, and vascular endothelial cells migrate, proliferate, and differentiate, forming granulation tissue. Finally, the granulation tissue matures and gradually transforms into a scar. Scarring, a consequence of skin damage, can affect aesthetics or lead to decreased skin function and psychological disorders, including low self-esteem and anxiety. Therefore, research is crucial to better prevent scarring, prevent impaired skin function, and improve skin appearance.
[0003] Scar formation is a complex physiological process involving the regulation of cell migration, inflammation, neural innervation, and angiogenesis, characterized by persistent local inflammation and excessive collagen deposition. Current clinical therapies for scar prevention and treatment include surgical, non-surgical, and combined therapies, including intralesional or topical steroids, cryotherapy, surgical excision, radiotherapy, and preventive laser therapy. These therapies have high success rates and low recurrence rates, but they are expensive and often associated with numerous adverse reactions. Therefore, developing an economical, safe, and effective drug delivery system to achieve scarless wound repair is of great clinical significance. Summary of the Invention
[0004] The purpose of the present invention is to make up for the shortcomings of existing clinical technology and provide a light-controlled liquefied hydrogel for inhibiting scar formation on wound surfaces, as well as its preparation method and application. The hydrogel has the characteristics of light-controlled liquefaction, precise drug release, good biocompatibility, and biodegradability, and is used to inhibit scar formation after wound healing.
[0005] The technical solution of the present invention is as follows: A light-controlled liquefied hydrogel for inhibiting scar formation, comprising the following components in parts by volume: 1-3 parts of PDA@CeO2-SAB nanoparticle suspension, 3-9 parts of borate borax buffer with pH 8.2-8.6, and 6-18 parts of 5-10 wt% PVA hydrogel; The concentration of the PDA@CeO2-SAB nanoparticle suspension is 160-200 μg / mL.
[0006] The present invention also provides a method for preparing a light-controlled liquefied hydrogel for inhibiting scar formation, comprising the following steps: 1) Preparation of PDA@CeO2-SAB nanoparticle suspension; 2) Preparation of boric acid borax buffer solution; 3) Preparation of PVA hydrogel; 4) Uniformly stir and mix the above materials to obtain the light-controlled liquefied hydrogel.
[0007] Further, in step 1, the preparation of PDA@CeO2-SAB nanoparticle suspension includes: 1A) Pluronic F127, dopamine hydrochloride and 1,3,5-trimethylbenzene are dispersed in a mixture of water and ethanol, an emulsion solution is formed by ultrasonic, ammonia water is added dropwise to the reaction mixture under stirring for oxidative self-polymerization, the product is collected by centrifugation after the reaction is completed, then washed with water and ethanol for several times, then resuspended with water to obtain PDA nanoparticle suspension; 1B) Ce(NO3)3·6H2O aqueous solution is added to the PDA nanoparticle suspension prepared in 1A) above, stirring to form a mixed solution, then sodium hydroxide solution is added to the above mixed solution for reaction, and dialysis is performed after the reaction is completed to obtain PDA@CeO2 nanoparticles; 1C) The PDA@CeO2 nanoparticles prepared in 1B) above are uniformly mixed with salvianolic acid B, and modification is carried out by stirring, then washed with pure water and freeze-dried after the reaction is completed to obtain PDA@CeO2-SAB nanoparticles, which are resuspended with water to obtain PDA@CeO2-SAB nanoparticle suspension.
[0008] Further, in step 1A), the temperature for oxidative self-polymerization is 20-30℃, and the time is 1-3 hours; In step 1B), the reaction temperature is 70-90℃, and the time is 5-10 hours; In step 1C), the modification temperature is 20-30℃, and the time is 20-30 hours.
[0009] Further, in 1A), the mass ratio of Pluronic F127 to dopamine hydrochloride is 4:3, and the volume ratio of 1,3,5-trimethylbenzene, water and ethanol is 7:250:250; the volume ratio of water to ethanol during washing is 1:1.
[0010] Further, in 1B), the concentration of Ce(NO3)3·6H2O aqueous solution is 4.60 mM, the concentration of PDA suspension is 0.38 mg / mL, and the volume ratio of the two is about 1:7.5, and the concentration of sodium hydroxide solution is 0.1 M.
[0011] Further, in step 2), the preparation of boric acid borax buffer solution includes: Mix 4.5 mL of 0.05M borate solution and 5.5 mL of 0.05M boric acid solution uniformly to obtain a boric acid borate buffer with pH of 8.4 as a crosslinking agent.
[0012] Further, the preparation step of the light-controlled liquefied hydrogel in step 4) comprises: (4A) First, 1-3 parts of PDA@CeO2-SAB nanoparticle suspension is uniformly mixed with 6-18 parts of 8% PVA hydrogel, and then 3-9 parts of boric acid borate buffer with pH of 8.4 is added and uniformly stirred, so that the PDA@CeO2-SAB nanoparticles are uniformly dispersed in the light-controlled liquefied hydrogel.
[0013] Compared with the prior art, the light-controlled liquefied hydrogel for inhibiting scar formation has the following advantages: (1) The hydrogel has good shape adaptability and adhesion, can change shape according to irregular wound surface, and firmly adheres to the wound surface without falling off, providing a moist repair environment for wound healing. The three-dimensional porous structure of the hydrogel is also beneficial to the permeation of oxygen, absorption of tissue exudate, reduction of inflammatory reaction of the wound surface, and promotion of wound healing. (2) The PDA@CeO2-SAB nanoparticles selected in the present application have good photothermal properties, can absorb 808 nm near-infrared light, and convert the light energy into heat energy. The heat energy generated can break the hydrogen bonds in the crosslinked network structure of the hydrogel, and the hydrogel is further liquefied to release the PDA@CeO2-SAB nanoparticles loaded therein, achieving precise drug release. In addition, the heat energy generated can also denature bacterial membrane proteins, achieving photothermal antibacterial effect. Compared with traditional antibiotic antibacterial therapy, the effect is better and the side effects are smaller. (3) It has been reported in the literature that c-JUN is highly expressed in scars, including hypertrophic scars and keloids. Combined with epigenomic and transcriptomic analysis of human and mouse hypertrophic scar fibroblasts, it was found that JUN induced fibrosis by regulating CD36. The use of SAB or CD36 knockout models reduced JUN-mediated fibrosis in human and mouse wounds. In the PDA@CeO2-SAB nanoparticles selected in the present application, SAB is an inhibitor of CD36, which can reduce the expression of CD36 protein in tissues and cells, thereby inhibiting the formation of scars on the wound surface. BRIEF DESCRIPTION OF DRAWINGS
[0014] Figure 1 The light-controlled liquefaction performance test results of Examples 1, 2, 3, and 4.
[0015] Figure 2 The biocompatibility test results of PCS PVA NIR in Example 6.
[0016] Figure 3 These are the test results of the PCS PVA NIR inhibitory effect on CD36 expression in 3T3 cells in Example 7.
[0017] Figure 4 These are the test results of the wound healing performance of PCS PVA NIR in Example 8. DETAILED DESCRIPTION
[0018] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials are commercially available unless otherwise specified.
[0019] In order to make the technical solutions and advantages of the present invention more clear and explicit, the specific implementation methods of the present invention are described in detail below with reference to specific examples. Example 1
[0020] (1A) 0.2 g of Pluronic® F127, 0.15 g of dopamine hydrochloride, and 0.28 mL of 1,3,5-mesitylene were dispersed in a mixture of 10 mL of water and 10 mL of ethanol. The mixture was sonicated for 5 minutes to form an emulsion. Subsequently, 0.75 mL of aqueous ammonia was added dropwise to the reaction mixture with stirring. After 2 hours of reaction, the product was collected by centrifugation (15,000 rpm, 10 minutes), washed several times with water and ethanol (1:1), and finally resuspended in water to prepare a PDA suspension. (1B) 0.67 mL of 4.60 mM Ce(NO3)3·6H2O aqueous solution was added to 5.0 mL of 0.38 mg / mL PDA suspension and stirred vigorously for 1 h. Then, 0.06 mL of 0.1 M sodium hydroxide was quickly added to the mixed solution and stirred at 80°C for 6 h. The obtained PDA@CeO2 nanoparticles were then dialyzed (molecular weight cutoff: 14 kDa). After 24 h, the liquid was collected to obtain PDA@CeO2 nanoparticles. (1C) PDA@CeO2 nanoparticles and salvianolic acid B (SAB) were uniformly mixed at a mass ratio of 8:1, stirred for 24 hours, and then freeze-dried to obtain PDA@CeO2-SAB nanoparticles; (1D) Mix 4.5 mL of 0.05 M borax solution and 5.5 mL of 0.05 M boric acid solution to obtain a borate-borax buffer solution with a pH of 8.4 as a cross-linking agent. (1E) 0.2 mL of 80 μg / mL PDA@CeO2-SAB nanoparticles and 1.2 mL of 8% PVA hydrogel were first stirred and mixed evenly, and then 0.6 mL of borate borax buffer with a pH of 8.4 was added and stirred evenly to ensure that the PDA@CeO2-SAB nanoparticles were evenly dispersed in the photo-controlled liquefied hydrogel.
[0021] The preparation method of 80 μg / mL PDA@CeO2-SAB nanoparticles is as follows: Weigh 1 mg of PDA@CeO2-SAB nanoparticles and dissolve them in 1 mL of water. Then aspirate 80 μL of the solution and dilute it to 1 mL with water. The preparation method of 8% PVA hydrogel is as follows: Weigh 4 g of PVA powder and dissolve it in 50 mL of pure water. Example 2
[0022] (2A) Same as Example (1A); (2B) Same as Example (1B); (2C) Same as Example (1C); (2D) Same as Example (1D); (2E) The concentration of PDA@CeO2-SAB nanoparticles was 120 μg / mL, and the rest of the procedures were the same as those in Example (1E). Example 3
[0023] (3A) Same as Example (1A); (3B) Same as Example (1B); (3C) Same as Example (1C); (3D) Same as Example (1D); (3E) The concentration of PDA@CeO2-SAB nanoparticles was 160 μg / mL, and the rest of the operation was the same as in Example (1E). Example 4
[0024] (4A) Same as Example (1A); (4B) Same as Example (1B); (4C) Same as Example (1C); (4D) Same as Example (1D); (4E) The concentration of PDA@CeO2-SAB nanoparticles was 200 μg / mL, and the rest of the procedures were the same as those in Example (1E).
[0025] Example 5 Photo-controlled liquefaction performance test of photo-controlled liquefaction hydrogel The photo-controlled liquefaction performance of the hydrogel was tested by the vial tilting method. 2 mL of the photo-controlled liquefaction hydrogels in Examples 1, 2, 3, and 4 were added to the vials at a power density of 1 W / cm 2 The 808 nm near-infrared laser was continuously irradiated on the hydrogel for 15 minutes. The temperature change of the hydrogel during these 15 minutes was recorded by the infrared thermal imager. After 15 minutes, the vial was tilted to observe the liquefaction of the hydrogel. Figure 1 As shown in the figure, after 15 minutes of 808 nm near-infrared laser irradiation, the temperature of the hydrogel increased with the increase of PDA@CeO2-SAB nanoparticle concentration. The temperature of the hydrogel group with 160 μg / mL PDA@CeO2-SAB nanoparticles exceeded 40°C after 15 minutes of irradiation, and the hydrogel began to show a certain degree of liquefaction.
[0026] Example 6 Cytocompatibility test of light-controlled liquefied hydrogel 1) Add 1 mL of the photo-controlled liquefaction hydrogel prepared in Example 4 of the present invention to 2 mL of complete culture medium containing 10% fetal bovine serum (FBS) and 1% double-antibody (penicillin / streptomycin). After incubation for 24 hours, aspirate the supernatant to obtain a photo-controlled liquefaction hydrogel extract; 2) Human umbilical vein endothelial cells (HUVEC) and mouse embryonic fibroblasts (3T3) were collected and seeded at 10,000 cells per well in a 96-well plate. Each well was incubated with 100 μL of the photoactivated liquefied hydrogel extract for 24 hours. The old culture medium was then discarded, and the cells were washed three times with PBS. 100 μL of fresh culture medium and 10 μL of CCK-8 solution were added and incubated for 1 hour. The absorbance at 450 nm was measured using a microplate reader, and the relative cell viability was calculated. 3) Culture cells as described above and stain them with a live-death staining kit (Calcein AM / Propidium Iodide). Observe the live-death status of cells using a laser confocal microscope. The results are as follows: Figure 2 As shown, the control group is a control, and the cell activity is above 80%, with no obvious cytotoxicity. Cell live-dead staining also shows that the cell morphology is normal, and there are no obvious dead cells, indicating that the light-controlled liquefied hydrogel prepared by the present invention has good biocompatibility.
[0027] Example 7 Testing of the performance of light-controlled liquefied hydrogel in inhibiting CD36 expression in 3T3 cells Immunofluorescence staining was used to detect CD36 expression in 3T3 cells to verify the ability of PCS PVA NIR to inhibit scar formation. Mouse embryonic fibroblasts (3T3) were collected and seeded at 80,000 cells per well in 12-well plates with seeded slides. The cells were incubated with 1 mL of photo-liquidized hydrogel extract for 24 hours. The old culture medium was then discarded, and the seeded slides were washed twice with PBS for 3 minutes each. The slides were fixed with 4% paraformaldehyde for 20 minutes and then washed twice with PBS. After permeabilization with 0.5% Triton X-100 at room temperature for 15 minutes, the cell slides were removed from the well plate, fixed at the four corners with nail polish on a slide, and washed three times with PBS for 3 minutes each time. The PBS was dried with absorbent paper, and 5% BSA was added to the slides at 100 μL / slide and blocked at 37°C for 30 minutes. The blocking solution was removed with absorbent paper, and CD36 primary antibody (50 μL / slide) was added. The slides were placed in a humidified chamber and incubated overnight at 4°C. The next day, the humidified chamber was removed and returned to room temperature for 1 hour. The slides were washed three times with PBS for 3 minutes each time, and Alexa Fluor 647-labeled goat anti-mouse secondary antibody was added at 100 μL / slide at 37°C for 30 minutes. The sections were washed three times with PBS for 3 minutes each time, and the liquid on the slides was dried with absorbent paper. The slides were mounted with mounting solution containing DAPI (staining cell nuclei: blue) and an anti-fluorescence quencher. The expression of CD36 in 3T3 cells was observed under laser confocal microscope. Figure 3 As shown, the Control group is the control, Figure 3 It can be seen that after applying the hydrogel extract of Example 4, the expression level of CD36 in 3T3 cells was significantly decreased, indicating that the light-controlled liquefied hydrogel prepared by the present invention has the ability to inhibit scar formation.
[0028] Example 8 Testing of the Performance of Light-Controlled Liquefied Hydrogel in Promoting Wound Healing Male C57BL / 6 mice aged 5-6 weeks and weighing 17-22 g were used to establish an acute infection wound model in mice. The mice were divided into 6 groups, with 9 mice in each group, namely the control group, PVA group, PVA NIR group, PDA@CeO2PVA NIR group (abbreviated as PC PVA NIR group), and PDA@CeO2-SAB PVA NIR group (abbreviated as PCS PVA NIR group). 1×10 7 The wound surface was covered with 3M dressing and bandaged; the PVA group was covered with PVA, and the wound surface was covered with 3M dressing and bandaged; the PVA NIR group was covered with PVA, and the wound surface was exposed to 808 nm (1 W / cm2 ) laser irradiation for 3 minutes, then apply medical 3 M dressing and bandage; PC PVA NIR group: PC PVA was applied to the wound surface, 808nm (1W / cm 2 ) laser irradiation for 3 minutes, then apply medical 3 M dressing and bandage; PCS PVA NIR group: PCS PVA was applied to the wound surface, 808 nm (1W / cm 2 After 3 minutes of laser irradiation, a medical 3M dressing was applied and bandaged. On days 0, 4, 7, 14, and 28, wound surface photographs were taken, wound size was counted, and wound closure rate was calculated. On day 4, the wound area in the control group accounted for 73.04%, while the wound area in the PCS PVA NIR group accounted for 6.48%. On day 7, the wound area in the control group accounted for 34.06%, while the wound area in the PCS PVA NIR group accounted for 1.33%. On day 14, the wound area in the control group accounted for 9.93%, while the wound area in the PCS PVA NIR group accounted for 0.93%. Figure 4 As can be seen from a and 4b, the wound healing rate in the hydrogel dressing group was faster than that in the control group. Figure 4 c It can be seen that the PCS PVA NIR hydrogel group healed the fastest after 808nm near-infrared light irradiation. Moreover, on the 28th day, the scar area of the control group accounted for 100%, and the wound area of the PCS PVA NIR group accounted for 0%. Figure 4 d It can be seen that the wound healing in the PCS PVA NIR hydrogel group was also better. After healing, the skin tissue was smooth and no scar was formed. This shows that the PCS PVA NIR hydrogel of the present invention has the effect of promoting wound repair and preventing scar formation.
[0029] The present invention provides a method for preparing and applying a light-controlled liquefied hydrogel that inhibits CD36 to achieve wound healing and scar repair. Numerous methods and approaches exist for implementing this technical solution. The above merely represents a preferred embodiment of the present invention. It should be noted that those skilled in the art could make various improvements and modifications without departing from the principles of the present invention, and such improvements and modifications are considered within the scope of the present invention. Any components not specified in this embodiment may be implemented using existing technologies.
[0030] The present invention belongs to the technical field of biomedical materials and discloses a light-controlled liquefied hydrogel for inhibiting wound scar formation, as well as its preparation method and application. The light-controlled liquefied hydrogel is composed of the following raw materials: 6 to 18 parts of PVA hydrogel, 3 to 9 parts of borax boric acid buffer, and 1 to 3 parts of PDA@CeO2-SAB nanoparticles. The hydrogel of the present invention has the characteristics of light-controlled liquefaction, precise drug release, inhibition of CD36 expression, good biocompatibility, and biodegradability. It can be used for infected wounds, providing a new, simple and effective material for inhibiting wound inflammation and resisting scar repair.
Claims
1. A light-controlled liquefied hydrogel for inhibiting scar formation, characterized in that: Calculated by volume, it includes the following components: 1-3 parts of PDA@CeO2-SAB nanoparticle suspension, 3-9 parts of borate borax buffer with pH 8.2-8.6, and 6-18 parts of 5-10 wt% PVA hydrogel; The concentration of the PDA@CeO2-SAB nanoparticle suspension is 160-200 μg / mL.
2. A method for preparing the light-controlled liquefied hydrogel according to claim 1, characterized in that: The following steps are involved: 1) Preparation of PDA@CeO2-SAB nanoparticle suspension; 2) Prepare borate borax buffer; 3) preparing PVA hydrogel; 4) The above materials are uniformly stirred and mixed to obtain the light-controlled liquefied hydrogel.
3. The method for preparing the light-controlled liquefied hydrogel according to claim 2, wherein: In step 1), the preparation steps of the PDA@CeO2-SAB nanoparticle suspension include: 1A) Pluronic® F127, dopamine hydrochloride, and 1,3,5-mesitylene are dispersed in a mixture of water and ethanol, and ultrasonically applied to form an emulsion solution. Aqueous ammonia is then added dropwise to the reaction mixture with stirring to cause oxidative polymerization. After completion of the reaction, the product is collected by centrifugation, washed several times with water and ethanol, and then resuspended in water to obtain a PDA nanoparticle suspension. 1B) adding a Ce(NO3)3·6H2O aqueous solution to the PDA nanoparticle suspension prepared in 1A) above, stirring to form a mixed solution, then adding a sodium hydroxide solution to the mixed solution for reaction, and dialyzing after the reaction to obtain PDA@CeO2 nanoparticles; 1C) The PDA@CeO2 nanoparticles prepared in 1B) above were uniformly mixed with salvianolic acid B and stirred to modify salvianolic acid B. After the reaction, the nanoparticles were washed with pure water and freeze-dried to obtain PDA@CeO2-SAB nanoparticles, which were then resuspended in water to obtain a PDA@CeO2-SAB nanoparticle suspension.
4. The method for preparing the light-controlled liquefied hydrogel according to claim 3, wherein: In step 1A), the temperature of the oxidative self-polymerization is 20-30° C. and the time is 1-3 hours; In step 1B), the reaction temperature is 70-90°C and the reaction time is 5-10 hours; In step 1C), the modification is performed at a temperature of 20-30° C. for 20-30 hours.
5. The method for preparing the light-controlled liquefied hydrogel according to claim 2, wherein: In step 2), the borate borax buffer solution is obtained by uniformly mixing a 0.04-0.06 M borax solution and a 0.04-0.06 M boric acid solution; The volume ratio of the borax solution to the boric acid solution is 4-5:5-6.
6. The method for preparing the light-controlled liquefied hydrogel according to claim 2, wherein: In step 4), the volume ratio of each component is PDA@CeO2-SAB nanoparticle suspension: borate borax buffer: PVA hydrogel = 1:3:
6.
7. The method for preparing the light-controlled liquefied hydrogel according to claim 2, wherein: The order of mixing the components in step 4) is as follows: first, the PDA@CeO2-SAB nanoparticle suspension and the PVA hydrogel are stirred and evenly mixed, and then the borate borax buffer solution is added and stirred evenly to obtain the light-controlled liquefied hydrogel.
8. A use of the light-controlled liquefaction hydrogel according to claim 1 or the light-controlled liquefaction hydrogel obtained by the preparation method according to any one of claims 2 to 7, characterized in that: The light-controlled liquefied hydrogel is used to prepare medical materials for promoting the repair of infected wounds.
9. The use according to claim 8, characterized in that The medical material is used for anti-scar repair of acute infected wounds.
Citation Information
Patent Citations
composition PVA-BASED HYDROGEL AS A FIBROBLASTIC GROWTH FACTOR
BR102015004157A2
Polyvinyl alcohol double-network hydrogel for wound surface as well as preparation method and application of polyvinyl alcohol double-network hydrogel
CN118059293A
Preparation and application of CeO2-coated PDA-GOD nano composite material
CN118217385A
Sterile medical wound repair hydrogel dressing and application thereof
CN120324665A
Wound dressing containing a chitosan / PVA(polyvinylalcohol) hydrogel and process for preparingthereof
KR1020020000580A
Cited By
Drug-loaded microgel-gel sustained-release dressing as well as preparation and application thereof
CN121465986A